Sacral Spina Bifida Occulta: A Frequency Analysis of Secular Change - Kelty, Ella R; Henneberg, Maciej (Anthropological Review, 2022)
Substantial relaxation of natural selection beginning around 1900 changed the mutation/selection balance of modern genetic material, producing an increase in variable anatomical structures. While multiple structures have been affected, the temporal increase in variations of the sacrum, specifically, ‘Sacral Spina Bifida Occulta,’ have been reliably demonstrated on a localised scale. Calculation of largescale frequency has been hindered by the localised nature of these publications, the morphological variability of this variation, and potential pathological associations, which have produced divergent classifications, and conflicting reported rates of occurrence. A systematic review of the reported literature was conducted to provide an objective analysis of Sacral Spina Bifida Occulta frequency from 2500 BCE to the present. This review was designed to compensate for observed inconsistencies in reporting and to ascertain, for the first time, the temporal trajectory of this secular trend. A systematic review of Sacral Spina Bifida Occulta literature was conducted through the strict use of clinical meta-analysis criteria. Publications were retrieved from four databases: PubMed, Embase, the Adelaide University Library database, and Google Scholar. Data were separated into three historical groups, (1 = 1980), and frequency outcomes compared, to determine temporal rates of occurrence.A total of 39/409 publications were included in the final analysis, representing data for 16,167 sacra, spanning a period of 4,500 years. Statistically significant results were obtained, with total open S1 frequency increasing from 2.34%, (79 to 1900CE), to 4.80%, (1900 to 1980CE) and to 5.43% (>1980CE). These increases were significant at p